Studies of structural-phase changes in a modified cement stone method by derivatographic analysis - Polonina, E.; Leonovich, S. (Ways to Improve Construction Efficiency, 2020)
The use of a complex nanodispersed additive consisting of a superplasticizer and nanoparticles (sol of nanosilica and carbon nanomaterial) have a significant effect on the hydration, hardening, and curing of building composites, predetermining their durability. The results of studies of phase transformations occurring in a cement stone modified with this additive are presented. The studies were carried out using the method of thermal analysis, which allows to obtain quantitative information about the change in the mass of the sample as a result of its heating and at the same time register this change. Thermal analysis has a number of advantages over other research methods, the flexibility of setting up an experiment, the rapid removal of information, the ability to automate data processing, and a small amount of substance. A comprehensive study of the properties of a material when it is heated allows a detailed and deeper study of the nature of the processes occurring in it. The study of physical and chemical processes was carried out on a combined thermogravimetric analysis device and differential scanning calorimetry METTLER TOLEDO, which is designed to measure the thermodynamic characteristics (heat and temperature of phase transitions and physico-chemical reactions), as well as detect changes in the mass of materials in the temperature range from 25 to 1600 degrees C. The article discusses the intervals of weight loss of samples containing an additive of superplasticizer and a complex nanodispersed additive in age those 1 and 28 days. To find out what effect a superplasticizer has on a cement sample, an additional sample No. 1, consisting only of cement and water, was examined at 28 days of age.